2020
DOI: 10.21203/rs.2.14706/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First-trimester maternal serum alpha-fetoprotein is not a good predictor for adverse pregnancy outcomes: a retrospective study of 3325 cases

Abstract: Background: It is well known that second-trimester maternal serum alpha-fetoprotein (MS-AFP) is a predictor for adverse pregnancy outcomes (APOs), such as preterm birth, stillbirth, preeclampsia and small for gestational age (SGA). However, it is unknown whether first-trimester MS-AFP is also predictive of APOs. Methods: We retrospectively reviewed the data on the first-trimester MS-AFP levels and pregnancy outcomes of 3325 singleton pregnant women. The cutoff value of 2.5 multiple of the median (MoM) was used… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Second trimester AFP, produced primarily by the fetal liver, has also been robustly linked to adverse pregnancy outcomes including preeclampsia, 58 with a large retrospective study (n=3325) reporting first trimester elevations, but poor predictive performance. 59 When combined, a ratio of AFP/PAPP-A above 10 resulted in a relative risk for severe preeclampsia of 2.12, with slightly improved (although not significant) area under the ROC curve (of 0.60 À reflecting only modest predictive potential) compared to either biomarker alone. 57 We have also assessed the potential of combining placental biomarkers to improve prediction.…”
Section: Placental Proteinsmentioning
confidence: 94%
“…Second trimester AFP, produced primarily by the fetal liver, has also been robustly linked to adverse pregnancy outcomes including preeclampsia, 58 with a large retrospective study (n=3325) reporting first trimester elevations, but poor predictive performance. 59 When combined, a ratio of AFP/PAPP-A above 10 resulted in a relative risk for severe preeclampsia of 2.12, with slightly improved (although not significant) area under the ROC curve (of 0.60 À reflecting only modest predictive potential) compared to either biomarker alone. 57 We have also assessed the potential of combining placental biomarkers to improve prediction.…”
Section: Placental Proteinsmentioning
confidence: 94%
“…Dieste-Pérez et alevaluated the relationship between first-trimester maternal serum free β-hCG and PAPP-A levels and pregnancy complications in 5297 pregnant women, 80 of whom were preeclamptic; PAPP-A and free β-hCG were significantly lower in the preeclamptic group than in the control group (Dieste-Pérez et al, 2022). It was found that 10% of preeclamptic pregnant women had PAPP-A levels below the 5th percentile and 7% of them had free β-hCG levels below the 5th percentile (Hu et al, 2020) Hendrix et al (2021 studied 8839 pregnant women, of whom 331 were preeclamptic. Similar to our study, the PAPP-A level was significantly lower in the preeclampsia group, whereas free β-hCG did not make a significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Moreover, the specificity of maternal serum AFP levels for NTD diagnosis can be disrupted by preeclampsia, placental damage, multiple births, or stillbirth. [25][26][27][28][29] In addition, maternal AFP seems to be sensitive to open NTDs, but not closed NTDs. 17 Thus, the diagnostic sensitivities and specificities of diverse NTD types are different, and maternal disease factors and improper fetal position that increase serum AFP levels can lead to misdiagnosis or missed diagnosis of NTDs.…”
mentioning
confidence: 97%